Efektivitas Dzikir terhadap Nyeri dan Kecemasan saat Sebelum Operasi dan Pasca Operasi: Literature Review & Meta Analysis - Ferriansyah, Yudha (Fahima, 2024)
One of the non-pharmacological measures that can be used to reduce perioperative anxiety is spiritual or religious intervention such as listening to Islamic praise (Dhikr). This study aims to determine the effectiveness of Dhikr on pain and anxiety before and after surgery. The methods used in the research are Literature Review and Meta-Analysis. A total of 1384 patients were included in this study. Of the 1384 patients, 796 patients were included in the Dhikr group and 588 patients were included in the no Dhikr group (Listening/humming songs or without any activity). The lowest heart rate value was in the Dhikr r group after surgery with a value of 81.6 ± 6.1 and the lowest respiratory rhythm value was in the Dhikr group before surgery with a value of 19.1 ± 0.9. Based on the pain score, it can be seen that the Dhikr group showed a significant reduction before surgery, 11.4 ± 20.5 compared to after surgery, 2.5 ± 3.5. This also occurred in other activity groups with a value of 12.1 ± 22.2 before surgery and 6.5 ± 12.3 after surgery. The anxiety score in the other activity group appeared to be lower at 8±7.8 compared to the Dzikir group at 24±16.7.